Differences Among Sexes in Blood Pressure: A Combinatorial Consequence of the Differences between RAAS Components, Sex Hormones, and Time Course - Yang, Xiaomei; Liu, Shien; Zhang, Zhongming (Current Hypertension Reviews, 2022)
For all lives regardless of sex, the longitudinal increase in blood pressure (BP) with age is attributed to lifestyle, internal environments like systemic brain-derived neurotrophic factor (BDNF) signaling, and external environments, allowing the individuals to better adapt to the developmental and environmental changes. Basic levels of renin-angiotensin-aldosterone system (RAAS) components in males and females define the fundamental sex difference in BP, which may be set by prenatal programming and the profound influence of BP after birth. The innate sex difference in BP is magnified during puberty growth and later on, affected and modified by menopause in women. At the age of 70 and older, blood pressure has been found to be similar for men and women. Understanding the prenatal setup and development of sexual dimorphism in BP may provide preventative therapeutic strategies, including timing and choice of drugs, for individuals with abnormal BP.
Keywords: time course